Estrategia para fomentar la transferencia de conocimiento en una entidad del sector defensa (2021)
People's knowledge and experience drive organizations growth. However, after reaching a level of expertise, people may change organizations or be transferred to another position, without knowledge being adequately transferred between staff members, which causes troubles in administrative management. This article presents a strategy for transferring the public entities processes related knowledge in a way that preserves it. It was a mixed approach study where a review of the literature on knowledge transfer in Spanish and English between 2000 and 2018 was included. A tool was applied to diagnose knowledge management based on Nonaka and Takeuchi theory. The final report of the four phases and the five facilitators yielded results below those expected, which demonstrated the entity shortcomings in that area. A proposal to promote knowledge transfer in the Management was developed and validated by experts. The reliability of the judgement was corroborated by Cronbach's alpha correlation coefficient and W Kendall's coefficient of concordance.